Impact and protagonism: peasant women facing the consequences of climate change - AArlla Katherine Xavier de Lima; Arthur Costa Pereira Santiago de Almeida; Alessandra Keilla da Silva; Crisea Cristina Nascimento de Cristo; José Roberto Santos (Universidade Estadual de Alagoas, 2023)
Climate change has several consequences that have profoundly affected women's lives, especially the lives of women farmers, as they belong to one of the most similar groups in society, and are even more supported by these changes. The impacts on agriculture significantly represented the lives of rural women, as they are responsible for producing part of the food that arrives at the table of the Brazilian people, despite this work being made invisible and seen as a mere help, peasant women have a primordial role in the production of healthy foods. The objective of this work is to analyze how peasant women are impacted by climate change and bring elements to think about public policies that encompass a gender, agroecological and intersectional perspectiv9e. The methodology used is qualitative and consists of performing a descriptive-analytical-reflective analysis through a bibliographic survey. In this way, it was possible to identify that peasant women are impacted by climate change differently from the context in which they are inserted. Women farmers have a strong bond with nature, they assume the role of guardians of natural resources and are on the front line in the fight against the destruction of the environment. It is through the empowerment and autonomy of these women that they are increasingly empowered and involved in the struggle for environmental sustainability and balance on planet earth.